2007
DOI: 10.1523/jneurosci.5265-06.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dlx-Dependent and -Independent Regulation of Olfactory Bulb Interneuron Differentiation

Abstract: Olfactory bulb interneuron development is a complex multistep process that involves cell specification in the ventral telencephalon, tangential migration into the olfactory bulb, and local neuronal maturation. Although several transcription factors have been implicated in this process, how or when they act remains to be elucidated. Here we explore the mechanisms that result in olfactory bulb interneuron defects in Dlx1&2 Ϫ/Ϫ (distal-less homeobox 1 and 2) and Mash1 Ϫ/Ϫ (mammalian achaete-schute homolog 1) muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
153
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(166 citation statements)
references
References 71 publications
(136 reference statements)
12
153
1
Order By: Relevance
“…In agreement with this finding, Dlx1 and Dlx2 expression was reported in the SVZ of the eminences coincident with Nrp-1, but complementary to what we found for Nrp-2 (Long et al, 2009b;Wang et al, 2011). The homeoproteins Dlx1 and Dlx2, identified to mediate the neuronal cell fate in Olig2 precursors of the basal telencephalon (Petryniak et al, 2007), were reported as crucial players in forebrain GABAergic neuron differentiation, migration, and survival (Anderson et al, 1997;Cobos et al, 2005Cobos et al, , 2007Long et al, 2007Long et al, , 2009a. Ghanem et al (2007) reported that distinct subtypes of cortical interneurons use different combinations of Dlx1/2 enhancers from the time of specification to adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…In agreement with this finding, Dlx1 and Dlx2 expression was reported in the SVZ of the eminences coincident with Nrp-1, but complementary to what we found for Nrp-2 (Long et al, 2009b;Wang et al, 2011). The homeoproteins Dlx1 and Dlx2, identified to mediate the neuronal cell fate in Olig2 precursors of the basal telencephalon (Petryniak et al, 2007), were reported as crucial players in forebrain GABAergic neuron differentiation, migration, and survival (Anderson et al, 1997;Cobos et al, 2005Cobos et al, , 2007Long et al, 2007Long et al, , 2009a. Ghanem et al (2007) reported that distinct subtypes of cortical interneurons use different combinations of Dlx1/2 enhancers from the time of specification to adulthood.…”
Section: Discussionsupporting
confidence: 89%
“…Given that the Dlx family of homeodomain proteins are master regulators of GABAergic neuron development, we first asked whether Rb deficiency results in a defect in the regulation of the Dlx1/Dlx2 bigene cluster, essential for interneuron development (Anderson et al, 1997(Anderson et al, , 2001Pleasure et al, 2000;Panganiban and Rubenstein, 2002;Stühmer et al, 2002;Long et al, 2007Long et al, , 2009; Petryniak et al, 2007). Using mice carrying a conditional telencephalic mutation for Rb (BF1-Cre; Rb flox/flox mice) (Hébert and McConnell, 2000;Marino et al, 2000), we examined the regulation of Dlx1 and Dlx2 in the developing telencephalon.…”
Section: Rb Is Required For Dlx1/dlx2 Gene Expression and Developmentmentioning
confidence: 99%
“…In the dorsal spinal cord, Ascl1 functions in specifying glutamatergic interneuron populations dI3 and dI5 (dorsal interneuron 3 and 5) (Helms et al, 2005). In telencephalon development, Ascl1 functions with Dlx2 to generate the GABAergic neurons that migrate to the cortex (Fode et al, 2000;Parras et al, 2002;Long et al, 2007). And in the peripheral nervous system, Ascl1 biases neural crest cells to the autonomic lin- eage rather than the sensory (Perez et al, 1999).…”
Section: Ascl1 Lineage Neurons In Adult Hippocampus and Olfactory Bulmentioning
confidence: 99%